Pablo & Birdy - McGhee, Alison, 1960-; Juan, Ana (New York : Atheneum, 2017)
Pablo, nearly ten, has many questions about his origins and how he arrived at Isla as a baby, but finding the answers may mean losing his lifetime companion, Birdy the parrot.
"A Caitlyn Dlouhy Book."
Keywords: Identity -- Fiction; Parrots -- Fiction; Human-animal relationships -- Fiction; Talking birds -- Fiction; Foster parents -- Fiction; Islands -- Fiction